Prevalence and associated factors of burn injury among primary school children in Sentul, Kuala Lumpur, Malaysia - Demado, Anusooya (2022)
Introduction: Burns are the fifth most common cause of non-fatal childhood injuries. Burns among children may not only cause life-long disability, but also affect the mental health and quality of life of their families, imposing a socioeconomic burden. There is limited availability of existing literature on home fires and burns among minors, traffic accidents and work-related injuries in Malaysia (Peck, 2011). In 2017, heat-related events caused more than 120 000 fatalities and close to 9 million injuries globally. Moreover, based on a report by Safe Kids, Universiti Putra Malaysia (UPM) highlighted that a child dies due to fire or burns very two weeks and 6.4% of parents said that they had experienced a fire at home in the previous two years (Kulanthayan et. al, 2016). The aim of this study is to measure prevalence of fire and burn related injuries at home and its associated factors. Hence, the development of preventive measures like training the communities in basic first aid and educating susceptible groups can greatly decrease the frequency and intensity of burn injuries since fire and burn accidents are largely preventable and it is necessary to evaluate parents' and kids' knowledge and consciousness. Objective: To explore the prevalence of burn injury and its associated factors among primary school children ages 7 to 11 years in Sentul, Kuala Lumpur. Methodology: Cross sectional study design was used to investigate the association between contributing factors and knowledge with prevalence of burn injury among 260 students ages 7 to 11 years and their respective parents from the government primary level schools in Sentul, Kuala Lumpur. The sampling method used for this study for the selection of schools was the probability sampling proportionate to size and for student sample selection was stratified random sampling. Validated and self-administered questionnaires was used for students and parents for data collection. All the data was analyzed using SPSS. Results: A total of 220 students participated in this study with response rate of 84.6%. Followed by the socio-demographic characteristics, 52% were male and the highest percentage of students (25%) were 8 years old. The majority were Malay students (56%). The majority of the students’ parents (31%) household income is RM1001 to 3000. The result shows that 31.8% had burn injury for the past one year. Out of 31.8% of burn injury incident, 18.2% caused by hot kitchen appliances/drinks/foods. The children had high knowledge on factors causing fire, burn and scald injury (65.9%), yet had low knowledge on first aid (84.5%) and fire response mechanism (74.5%). The parents had high knowledge on first aid for burns (53.4%) and fire response mechanism (60.9%). Multiple logistic regression analysis revealed that child living in apartment/flat/condominium types of houses were 2.504 times more likely to have burn injury compared to Terrace/Lowcost/ Wood. Children with low knowledge on factors causing fire, burn and scald injury have increased odds of burn injury by 1.112 times (AOR = 1.112, 95% CI =1.020-2.342, p = 0.028). Parents with low knowledge on first aid for burns tripled the odds of burn injuries among children (AOR = 3.223, 95% CI = 1.234-4.567, p <0.001). Parents with low knowledge on burn preventive measures fire response mechanism have doubled the odds of burn injuries among children (AOR = 2.556, 95% CI = 1.642-4.882, p = 0.021). Conclusion: Despite having acceptable knowledge of burn injury factors, the children lacked knowledge of burn first aid care and fire response mechanism. It is possible that this is due to a lack of awareness programs and inadequate burn first aid management and fire response mechanism education in the school curriculum. The use of various methods of education to teach about the key principles of burn first aid management and fire response mechanism may be expanded upon in school topics. To raise parental knowledge of burn hazards, educational programs targeted at detecting and avoiding the causes of burn injuries are critical, particularly for those who live in apartments, flats, or condominiums. Governmental and non-governmental organizations should make much greater efforts to increase awareness among the parents and to reduce the prevalence of burn injury.